PROBLEM OF IMAGINATION IN PSYCHOLOGY (on the example of analysis of the construction of verbal images) - Shragina , L. I. (Modern Psychology, 2019)
The presence of a wide range of views on the phenomenon of "imagination" as the psychological basis of creative activity to developing new material and spiritual values suggests that this phenomenon in the scientific view is still a problem. At the core of the problem is a contradiction: there is a creative activity that is carried out through imagination, but imagination itself as a phenomenon disappears during analysis, which makes it necessary to consider it on the basis of a fundamentally new methodological approach. As a methodology proposed functional system approach. Considered, on the basis of the proposed approach, the functioning of the verbal imagination in the process of creating a verbal image as an artificial system. In terms of the functional system approach, “verbal imagination” is defined as a metasystem - a complex of certain mental operations (actions) of a subject that arises and functions only when the subject needs to control and manage his cognitive processes during the creation of a verbal image.
Keywords: artificial system, functional-system approach, metasystem, verbal imagination, metacognitive processes.